Fantasy Sports and the Changing Sports Media Industry: Media, Players, and Society - Philippe-Antoine Lupien (Communiquer)
This book review focuses on the book Fantasy Sports and the Changing Sports Media Industry, co-edited by Nicholas David Bowman, John S. Spinda and Jimmy Sanderson (2016). It combines about fifteen articles that tend to lay the framework of a study on fantasy sports by sharing historical and emerging perspectives on this entertainment form which recently emerged, namely through the development of digital information and communication technologies.